Trade, technology, and absorptive capacity: Firm-level evidence across geographical clusters in the Tanzanian textiles and apparel sector - Amrita Saha; André Castro; Marco Carreras; Daniele Guariso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Trade-linked technological change has potential to increase incomes in low-income countries (LICs). The most labour-intensive segments of the textiles and apparel global value chain are in LICs. However, gaps between available technologies and best practices make it difficult to adopt more efficient production processes or move into higher value-added functions. This paper examines current technology use in the Tanzanian textiles and apparel sector, using nationally representative secondary data, primary quantitative data, and qualitative information from semistructured interviews. First, we examine whether firms' absorptive capacity mediates the effect of imported technology on firm productivity. Second, we look at differences across geographical clusters of firms in terms of local linkage types. Third, we assess current technology, gaps in firms' capabilities, and challenges in the sector to identify policy implications. Finally, we provide brief reflections on how firms in the Tanzanian textiles and apparel sector may adapt in the postCOVID-19 recovery phase.
Keywords: D22; D24; O14; O32; 330; absorptive capacity; firm productivity; global value chain; Tanzania; textiles andapparel